Asking before Arguing? Consent in Argumentation - Stevens, Katharina (Ethical theory and moral practice, 2025)
Arguments involve, at minimum, attempts at presenting something that an audience will take to be a reason. Reasons, once understood, affect an addressee’s beliefs in ways that are in some significant sense outside of their direct voluntary control. Since such changes may impact the well-being, life projects, or sense of self of the addressee, they risk infringing upon their autonomy. We call this the "autonomy worry" of argumentation. In light of this worry, this paper asks whether one ought to seek an addressee’s consent before arguing with them. We first consider the view that arguing of any sort and on any topic requires consent. However, such a view is extreme, and we reject the general requirement of consent because argument contains its own internal permission structure. We find, however, that this permission structure is not always operative, and that consent may nonetheless be morally required in certain kinds of cases.